Regulating the interactions between climate change and groundwater: lessons from India. Issue 6 (18th August 2017) - Cullet, Philippe; Bhullar, Lovleen; Koonan, Sujith
ABSTRACT: Groundwater is often considered a largely local issue that is difficult to regulate. Further, groundwater regulation has often focused on use, rather than protection and conservation. There has thus been little integration of environmental concerns into groundwater regulation. Climate change calls for rethinking the regulatory framework for protecting and regulating groundwater. In India, the climate change regime has not given groundwater adequate prominence. Conversely, groundwater regulation remains largely detached from environmental challenges, including climate change. This needs to be addressed through regulation that links the two fields and is based on legal principles derived from the Constitution of India.